2001
DOI: 10.1096/fj.99-1003rev
|View full text |Cite
|
Sign up to set email alerts
|

The soluble interleukin 6 receptor: mechanisms of production and implications in disease

Abstract: Interleukin 6 (IL-6) performs a prominent role during disease and has been described as both a pro- and anti-inflammatory cytokine. A key feature in the regulation of IL-6 responses has been the identification of a soluble interleukin 6 receptor (sIL-6R), which forms a ligand-receptor complex with IL-6 that is capable of stimulating a variety of cellular responses including proliferation, differentiation and activation of inflammatory processes. Elevated sIL-6R levels have been documented in numerous clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
481
1
13

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 555 publications
(507 citation statements)
references
References 173 publications
5
481
1
13
Order By: Relevance
“…IL-6 signaling can be triggered by two separate pathways [34]. In classical signaling, IL-6 influences cellular responses by binding to a specific IL-6 cell surface receptor subunit (IL-6Rα).…”
Section: Elucidation Of An Il-6 Trans-signaling Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 signaling can be triggered by two separate pathways [34]. In classical signaling, IL-6 influences cellular responses by binding to a specific IL-6 cell surface receptor subunit (IL-6Rα).…”
Section: Elucidation Of An Il-6 Trans-signaling Mechanismmentioning
confidence: 99%
“…For example, lymphocyte recruitment to areas of inflammation has been linked to an IL-6 trans-signaling mechanism in autoimmune states such as rheumatoid arthritis and inflammatory bowel disease [34]. It is believed that IL-6 trans-signaling also triggers the transition from innate immunity to acquired immunity by selectively regulating chemokine and adhesion molecule-dependent recruitment of leukocyte subsets to inflamed tissues [51].…”
Section: Clinical Implications Of Thermal Therapy Dynamicsmentioning
confidence: 99%
“…There is compelling evidence that augmented levels of IL-6 are associated with several metabolic diseases, including type 2 diabetes and cardiovascular disease (3)(4)(5)(6). IL-6 acts via a receptor complex consisting of two functional membrane proteins: an 80-kDa ligand-binding IL-6 receptor and a 130-kDa signal transducer (gp130) (7,8). Soluble and active forms of the extracellular domain of the IL-6 receptor, which is produced both by differential splicing of the IL-6 receptor transcript and by proteolytic cleavage of the protein in a process termed shedding, are also found in normal serum and synovial fluids.…”
mentioning
confidence: 99%
“…Once bound to IL-6, the resulting IL-6/sIL-6R complex acts as an agonist that is capable of activating cells through gp130. 21 Several studies showed that IL-6/sIL-6R complex could induce proliferation of synovial fibroblastic cells. 50 Moreover, the IL-6/sIL-6R complex has been reported to regulate leukocyte recruitment and to promote proinflammatory stimulation of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…19 Central to regulation of IL-6-mediated responses is the presence of soluble IL-6 receptor (sIL-6R), which forms a ligand-receptor complex allowing IL-6 responsiveness in cell types not expressing IL-6R. 20,21 This IL-6/sIL-6R complex can activate cells that do not normally respond to IL-6 through interaction with gp130. Although sIL-6R is released into body fluids of normal individuals, high levels of sIL-6R are associated with various diseases [22][23][24][25][26] by promoting a number of biological responses.…”
mentioning
confidence: 99%